2013
DOI: 10.4274/tjh.2013.0042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omeprazole on Iron Absorption: Preliminary Study

Abstract: None declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Tempel et al 8 showed no effect on iron absorption with short-term PPI therapy. Some studies suggest that prolonged omeprazole use for at least 3 to 4 years is unlikely to cause iron and ferritin malabsorption, 6 whereas Sarzynski et al 9 found that among adults on long-term PPI therapy, defined as >1 year, there was a significant decrease in hematologic indices from baseline.…”
Section: Discussionmentioning
confidence: 95%
“…Tempel et al 8 showed no effect on iron absorption with short-term PPI therapy. Some studies suggest that prolonged omeprazole use for at least 3 to 4 years is unlikely to cause iron and ferritin malabsorption, 6 whereas Sarzynski et al 9 found that among adults on long-term PPI therapy, defined as >1 year, there was a significant decrease in hematologic indices from baseline.…”
Section: Discussionmentioning
confidence: 95%
“…Iron is absorbed in the ferrous form in the duodenum via a divalent metal transporter-1 (DMT1) [5]. Nonheme iron, in contrast to heme or animal iron, requires gastric acid to reduce its ferric to ferrous form and so facilitate its absorption [6]. Reduction of gastric acid production by pharmacological means may therefore reduce the bioavailability of nonheme iron.…”
Section: Introductionmentioning
confidence: 99%